The Roots and Remedies of Social Violence: A Global Narrative Review - Widyanti, Eka; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2024)
Violence in social and occupational settings remains a pressing global concern, affecting individual well-being and societal cohesion. This narrative review aims to explore the causes, contexts, and interventions surrounding violence, drawing from multidisciplinary literature. The review utilized a structured search strategy across major scientific databases, including Scopus, PubMed, and Web of Science, incorporating studies that focused on workplace violence, intimate partner violence, aggression, and mental health. Key inclusion criteria encompassed peer-reviewed articles published in English and involving populations directly exposed to violence. Findings reveal that the main drivers of violence include high-stress work environments, inadequate support systems, cultural gender norms, and adverse childhood experiences. These factors contribute to elevated rates of mental health disorders such as PTSD, depression, and anxiety, particularly among women, children, and individuals with disabilities. Interventions such as educational programs (e.g., Irie Classroom Toolbox), peer-support initiatives, and trauma-informed training for professionals have shown promise in reducing the impact of violence. Systemic and structural influences, including social inequality, weak legal protections, and cultural stigma, were found to exacerbate vulnerability and impede access to help. The review highlights the importance of context-specific, community-based strategies in resource-limited settings and policy reform in institutional contexts. Future research should focus on inclusive longitudinal studies and leverage digital tools for violence monitoring and prevention. Addressing violence requires a coordinated, multi-layered approach that combines education, mental health access, and systemic reform.